Deviation of Management of Medical Waste from Hospital Implication upon Environmental Damage in West Sumatera, Indonesia - Alhamda, Syukra; Barlian, Eri; Razak, Abdul; Riyadi, Bambang Slamet; Herawati, Nova; Anggara, Ariff Trisetia (International Journal of Criminology and Sociology, 2022)
The purpose of this study is to show and analyze suspected abuse of power by hospital administrators in North Sumatra with public officials, in this case the bureaucrats in the Ministry of Environment of West Sumatra Region, carrying out hazardous medical waste out of place according to environmental science regulations, so that it occurs environmental damage. This research approach method is a qualitative method. Creswell defines a qualitative method as a research method that is based on the perspective of constructivism, namely various meanings, meanings that are socially and historically constructed with a view to developing a theory or pattern. Researchers collect data that is open-ended and developing, with the aim of developing a theme from the data obtained. The data collection technique is carried out by literature study of primary and secondary and tertiary legal materials. Environmental regulation analysis techniques, with analysis using the theory of abuse of power. So that researchers draw conclusions deductively, and provide recommendations or suggestions according to research objectives The results found here were that the actors of the management of hospital medical waste disposal were not in accordance with hospital regulations and environmental regulations. Suggestions are provided by researchers for environmental crime prevention in an effort to prevent and tackle environmental destruction.